NALAR KRITIS HUKUM ISLAM TERHADAP RESPON MODERNITAS - Edy Imam Supneo; Ansari Ansari (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Islamic law will still be able to respond to new issues arising, as a consequence of the advancement of science and technology. In the Treasures of Islamic Sciences, Fiqh (Islamic law) is one of the classical disciplines that are always loaded with interesting discourse, the natural character of the Islamic law as part of the Islamic Shari'a and permanent (qath'i) and must be received "taken for granted" on one side and his position as a product of Ijtihadi which is often produced from the relatively Islamic sources (Zhanny) on the other hand makes Islamic law has a different face. In other words, Islamic law is often identical to the number of rules and doctrines of Islam on some daily issues of Islamic Ummah which is static and raw. Among the emerging laws of the world are laws that are based on religious norms. Because religion always strengthens and closely interwoven with the state of Islamic law is one of the religious norms that exist in the world of Islamic law is universal, because it bases its various conditions based on Maqashid al-Syari'ah, namely Hifzhu al-Din, Al-Nafs, Al-Aqli, Al-Nasi, an al-Amal, which are all closely related to human life, both in ancient and modern times. Besides, Islamic law prioritizes the principles of truth, fairness, equality, and responsibility.